Modeling the optimal structure of the incentive payments fund of an organization - Kupryushina O.M, Endovitsky D.A, Davnis V.V., (Opción, 2019)
The article reveals the author’s approach to optimizing the fund of university incentive payments. The proposed model allows to structure the existing fund of incentive payments in such a way as to increase the average level of faculty salaries. As a result, a change in the structure of incentive allowances at a constant amount has a noticeable effect on the average wage level. In conclusion, due to an increase in average wages, one can achieve a higher place in domestic and international ratings of higher education institutions.